Modelling SPECT auto-contouring acquisitions for 177Lu & 131I molecular radiotherapy using new developments in Geant4/GATE. (April 2022) - Kayal, Gunjan; Chauvin, Maxime; Mora-Ramirez, Erick; Clayton, Naomi; Vergara-Gil, Alex; Tran-Gia, Johannes; Lassmann, Michael; Calvert, Nicholas; Tipping, Jill; Struelens, Lara; Bardiès, Manuel; ,
Highlights: Auto-contour SPECT modelling (step & shoot acquisition). Phantom SPECT projection simulation and validation against experiments. Importance of auto-contour modelling on radionuclide with high septal penetration. Extend auto-contour modelling to a context of clinical dosimetry. Abstract: Purpose: Monte Carlo modelling of SPECT imaging in Molecular Radiotherapy can improve activity quantification. Until now, SPECT modelling with GATE only considered circular orbit (CO) acquisitions. This cannot reproduce auto-contour acquisitions, where the detector head moves close to the patient to improve image resolution. The aim of this work is to develop and validate an auto-contouring step-and-shoot acquisition mode for GATE SPECT modelling. Methods: 177 Lu and 131 I SPECT experimental acquisitions performed on a Siemens Symbia T2 and GE Discovery 670 gamma camera, respectively, were modelled. SPECT projections were obtained for a cylindrical Jaszczak phantom and a lung and spine phantom. Detector head parameters (radial positions and acquisition angles) were extracted from the experimental projections to model the non-circular orbit (NCO) detector motion. The gamma camera model was validated against the experimental projections obtained with the cylindrical Jaszczak ( 177 Lu) and lung and spine phantom ( 131 I). Then, 177 Lu and 131 I CO and NCO SPECT projections were simulated to validate the impact of explicit NCO modelling on simulated projections. Results: Experimental and simulated SPECT images were compared using the gamma index, and were in good agreement with gamma index passing rate (GIPR) and gammaavg of 96.27%, 0.242 ( 177 Lu) and 92.89%, 0.36 ( 131 I). Then, simulated 177 Lu and 131 I CO and NCO SPECT projections were compared. The GIPR, gammaavg between the two gamma camera motions was 99.85%, 0.108 for 177 Lu and 75.58%, 0.6 for 131 I. Conclusion: This work thereby justifies the need for auto-contouring modelling for isotopes with high septal penetration.